Some thoughts about the “Consensus statement on smoking and vascular risk” from the Spanish Autonomous Societies of Hypertension and Vascular Risk - Javier Nieto Iglesias; Alfonso Pobes Martínez de Salinas; Nicolás Roberto Robles Pérez-Monteoliva (Nefrología (English Edition))
Smoking is a known preventable risk factor for vascular diseases. However, it is one of the most forgotten risks when we talk about its relationship with kidney disease. Following the publication of the “Consensus statement on smoking and vascular risk” promoted by the autonomous societies of hypertension and vascular risk of Spain, we consider that the nephrology community should be alerted about the deleterious effects of exposure to tobacco smoke and its consequences on renal damage. Something to take into account given the prevalence of smoking in our environment, approaching its prevention and treatment. Resumen: El consumo de tabaco es un conocido factor de riesgo evitable para las enfermedades vasculares, sin embargo, parece uno de los grandes olvidados cuando hablamos de su relación con la enfermedad renal. A raíz de la publicación del “Documento de consenso sobre tabaquismo y riesgo vascular” promovido por las sociedades autonómicas de hipertensión y riesgo vascular de España, consideramos que se debe alertar a la comunidad nefrológica sobre los deletéreos efectos por los que la exposición al humo del tabaco daña el riñón. Algo a tener muy en cuenta, por la prevalencia del tabaquismo en nuestro medio, además de su tratamiento y prevención.